The Weird Impossibility of Story - Hegyi, Pál (Hungarian Journal of English and American Studies, 2020)
What do we read in horror stories? To answer such an elusive question, research both historic and theoretical in nature is necessary. A comparison of proto-horror fiction by highly canonized nineteenth-century and early twentieth-century American authors (Poe, Bierce, James, Harvey, and Gilman) as well as Lovecraftian poetics reveals the presence of a theoretical thread that sutures these seemingly disparate literatures together. Classic American short stories show a strikingly similar memetic conformation to weird fiction when examined from the framework offered by Sigmund Freud’s seminal essay “Das Unheimliche” [The Uncanny] (1919). Identifying the memetic transmutations that the uncanny goes through in various close readings offers a taxonomy of six tropes—allegorizations of singularities, doubles, and triads—that are already implicit in the Freudian text. Such categorization applied to the weird genre unravels poetics that, as the article argues, stem from an innately subversive impulse in American literature. (PH)